2014 White Paper on recent issues in bioanalysis: a full immersion in bioanalysis (Part 3 – LBA and immunogenicity). (December 2014) - Stevenson, Lauren; Amaravadi, Lakshmi; Myler, Heather; Salazar-Fontana, Laura; Gorovits, Boris; Kirshner, Susan; Xue, Li; Garofolo, Fabio; Alley, Stephen C; Thway, Theingi; Joyce, Alison; Bansal, Surendra; et al.
The 2014 8th Workshop on Recent Issues in Bioanalysis (8th WRIB), a 5-day full immersion in the evolving field of bioanalysis, took place in Universal City, California, USA. Close to 500 professionals from pharmaceutical and biopharmaceutical companies, contract research organizations and regulatory agencies worldwide convened to share, review, discuss and agree on approaches to address current issues of interest in bioanalysis. The topics covered included both small and large molecules, and involved LCMS, hybrid LBA/LCMS, LBA approaches and immunogenicity. From the prolific discussions held during the workshop, specific recommendations are presented in this 2014 White Paper. As with the previous years' editions, this paper acts as a practical tool to help the bioanalytical community continue advances in scientific excellence, improved quality and better regulatory compliance. Due to its length, the 2014 edition of this comprehensive White Paper has been divided into three parts for editorial reasons. This publication (Part 3) covers the recommendations for Large molecules bioanalysis using LBA and Immunogenicity. Part 1 (Small molecules bioanalysis using LCMS) and Part 2 (Hybrid LBA/LCMS, Electronic Laboratory Notebook and Regulatory Agencies' Input) were published in the Bioanalysis issues 6(22) and 6(23), respectively.